2013
DOI: 10.2478/s11533-012-0131-6
|View full text |Cite
|
Sign up to set email alerts
|

Collineation group as a subgroup of the symmetric group

Abstract: Let ψ be the projectivization (i.e., the set of one-dimensional vector subspaces) of a vector space of dimension ≥ 3 over a field. Let H be a closed (in the pointwise convergence topology) subgroup of the permutation group $\mathfrak{S}_\psi $ of the set ψ. Suppose that H contains the projective group and an arbitrary self-bijection of ψ transforming a triple of collinear points to a non-collinear triple. It is well known from [Kantor W.M., McDonough T.P., On the maximality of PSL(d+1,q), d ≥ 2, J. London Math… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 13 publications
(17 reference statements)
0
13
0
Order By: Relevance
“…If F is infinite of characteristic p with prime subfield F p , then V has as a proper non-trivial definable reduct (and group-reduct) the structure of a vector space over F p , and intermediate fields give intermediate reducts. 6. Let F = (F, +, ×) be an algebraically closed field.…”
Section: Other Possible Examplesmentioning
confidence: 99%
See 2 more Smart Citations
“…If F is infinite of characteristic p with prime subfield F p , then V has as a proper non-trivial definable reduct (and group-reduct) the structure of a vector space over F p , and intermediate fields give intermediate reducts. 6. Let F = (F, +, ×) be an algebraically closed field.…”
Section: Other Possible Examplesmentioning
confidence: 99%
“…In an earlier version of this paper we also asked whether the groups PGL(n, Q) (for 3 ≤ n ≤ ℵ 0 ) are maximal-closed, and more generally whether Sym(N) has any countable maximalclosed groups. However, both these questions are answered positively in [7], where it is shown that if H > PGL(n, F) is closed (F any field) and contains a permutation taking a collinear triple to a noncollinear triple, then H is the full symmetric group.…”
Section: Claim 3 There Is a Cone Of M Definable By An L -Formula φ(Xmentioning
confidence: 99%
See 1 more Smart Citation
“…Several related questions have recently been tackled. Independently, [3] and [9] showed that there exist nonoligomorphic maximal-closed subgroups of Sym(N), the existence of which was asked in [16]. Also, independently, [17] and [9] positively answered Macpherson's question of whether there are maximal-closed subgroups of Sym(N) of countable cardinality.…”
mentioning
confidence: 99%
“…Independently, [3] and [9] showed that there exist nonoligomorphic maximal-closed subgroups of Sym(N), the existence of which was asked in [16]. Also, independently, [17] and [9] positively answered Macpherson's question of whether there are maximal-closed subgroups of Sym(N) of countable cardinality. One question that remains open is whether every proper closed subgroup of Sym(N) is contained in a maximal-closed subgroup of Sym(N), (Question 7.7 in [21] and Question 5.9 in [3]).…”
mentioning
confidence: 99%